CuCl2 anchored on polydopamine coated-magnetic nanoparticles (Fe3O4@PDA/Cu(II)): Preparation, characterization and evaluation of its cytotoxicity, antioxidant, antibacterial, and antifungal properties. (1st February 2020) - Hemmati, Saba; Zangeneh, Mohammad Mahdi; Zangeneh, Akram
Graphical abstract: Abstract: In recent years, biosynthesis of metallic nanoparticles has gained much attention for the treatment of fungal and bacterial diseases. The purpose of the study was preparation, characterization, and assessment of cytotoxicity, antioxidant, and antimicrobial properties of CuCl2 coordinated on polydopamine coated-magnetic nanoparticles (Fe3 O4 @PDA-CuCl2 ). These nanoparticles were characterized by FT-IR, FE-SEM, TEM, EDS, ICP, and XPS analysis. According to the TEM and SEM analysis, Fe3 O4 @PDA-CuCl2 showed uniform spherical morphology and average diameters of 10–20 ± 5 nm. In the biological part of this study, Fe3 O4 @PDA-CuCl2 have significant cell viability against HUVECs line, inhibitory activities against common free radical i.e., DPPH, antibacterial potentials against Gram-negative bacteria ( Salmonella typhimurium, Listeria monocytogenes, Proteus mirabilis, Escherichia coli O157:H7, and Pseudomonas aeruginosa ) and Gram-positive bacteria ( Streptococcus pneumonia, Enterococcus faecalis, Staphylococcus saprophyticus, Staphylococcus aureus, and Bacillus subtilis ), and antifungal properties against Candida guilliermondii, Candida parapsilosis, Candida albicans, Candida krusei, and Candida glabrata . The results of FT-IR, FE-SEM, TEM, EDS, ICP, and XPS confirm the biosynthesis of Fe3 O4 @PDA-CuCl2 with a notable amount of antioxidant, antimicrobial, and cutaneous wound healing effects.